Estimation of stress tolerance indices for identification of heat tolerant genotypes in barley - Yogender Kumar*, Suman Devi, Divya Phougat and Harsh Chaurasia (Electronic Journal of Plant Breeding)
The objective of present study was to assess the heat tolerance of barley genotypes employing a set of 12 heat stress indices namely SSI, TOL, STI, SSPI, YI, YSI, RSI, MP,GMP, HM, MRP and RED, estimated using grain yield. A total of 29 barley genotypes were evaluated under normal (non-stress) and heat stress conditions during 2021-22 crop season with four replications in randomized block design (RBD) at Research Area, Department of Genetics and Plant Breeding, CCS Haryana Agricultural University, Hisar (Haryana). The genotypes, DWRB 91, BH 20-40, BH 20-05, BH 20-07 and BH 19-15 were found to be heat tolerant based on average rank of SSI for different traits. However, based on overall rank of stress indices employed on grain yield, BH 19-13, BH 20-40, BH 393, BH 19-15, BH 20-02 and BH 946 were found prominent with tolerance to heat stress. Grain yield (Ys) showed negative association with SSI, RSI and RED and significant positive correlation with the indices viz., STI, YI, MP, GMP and HM. Hence these indices could be regarded as the best selection indicators for heat stress tolerance. PCA study considered second principal component (PC 2) as heat tolerant component based on strong correlation with STI, YI, YSI, MP, GMP, HM, MRP and Ys under stress condition. The genotypes of cluster I exhibited better performance under stress condition for grain yield (Ys) and SSI, TOL, SSPI, RSI, RED, YI, YSI, and MRP. The genotypes from this group could be utilized as promising breeding material for development of new heat tolerant barley cultivars.